In Good Company: Comments (American Journal of Islam and Society, 2018)
This article is part of Darakhshan Khan’s larger body of work on womenin the Tablīghī Jamā‘at, who, as she argues persuasively, have not been giventhe scholarly attention they deserve (barring a few notable exceptions,among them Metcalf 2000). Khan observes that the reasons for this rangefrom the fact that the public image of the Tablīghī Jamā‘at is that of itinerantmales, not females, and that gender segregation in South Asian Muslimcommunities makes women invisible to male scholars. Moreover, in today’spost-9/11 world the Tablīghī Jamā‘at is often viewed through the lens ofcounter-terrorist concerns.Khan’s article revolves around several key themes: the geographicalmobility of Muslim bureaucrats in late nineteenth-century British India;changes in the structure of the family; changing patterns of religious leadershipin British India, resulting in part from the creation of seminaries suchas the Dār al-‘Ulūm, Deoband; and the incorporation of Muslim womenin religious leadership roles in Tablīghī networks from the mid-twentiethcentury onward. The article seems to fall into two distinct parts. The firsthalf deals with Muslim men from ashraf families working in British Indiangovernment jobs in the late nineteenth century who moved constantly(with their wives and children) in response to bureaucratic postings, livingwesternized lives at the margins of highly stratified British Indian socialnetworks. Drawing on sources ranging from Urdu literature to biographies,Khan shows how isolating this was for the wives and sometimes professionallydisappointing for the husbands. The second half of the article dealswith Muslim religious elites and their more limited geographical travelsin British India in pursuit of religious knowledge, often coinciding with ...